Program Bimbingan dan Konseling di Sekolah - Mustofa, Mustofa; Shukatin, Shukatin; Fahrezi, Fajar; Haqiqi, Adif Farhian (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
The school guidance and counseling program plays a crucial role in supporting students’ academic, personal, and social development. This study aims to evaluate its effectiveness in addressing academic challenges, social adaptation, emotional well-being, and career planning. Using a qualitative approach, data were collected through interviews with counselors, teachers, and students, as well as document analysis. The results show that structured counseling programs positively impact students’ academic performance and emotional stability while fostering career readiness. Key services such as individual and group counseling, career guidance, and preventive programs contribute to a supportive learning environment. However, challenges like limited counselor availability and students' reluctance to seek help remain. Enhancing collaboration among stakeholders and integrating digital platforms can improve the effectiveness of these programs, ensuring students receive optimal support for their overall development and future success.